Development of nanostructured ceramic coatings from suspension and solution precursor thermal spraying process - Owoseni, Tunji Adetayo (2021)
The need for high performance, low emission gas turbine engines is driving development of new coatings with bespoke compositions and microstructure to increase thermal efficiency and reduce wear of engine parts. Alumina (Al2O3) is suitable in wear applications while yttria stabilized zirconia (YSZ) has been the standard topcoat material for thermal barrier coatings (TBC). The shortcomings of YSZ have spurred the search for new materials and/or processing techniques. Al2O3 coatings are traditionally deposited using feedstock of its stable polymorph, α–Al2O3; despite the availability and low cost of metastable Al2O3 feedstock, the metastable Al2O3 feedstock is yet to be explored for wear applications. This thesis presents the study on coatings made of yttrium aluminium garnet (YAG) as potential alternative to YSZ for thermal barrier coating and Al2O3 coating produced from metastable Al2O3 feedstock for wear application—all the coatings investigated were produced using high-velocity oxy-fuel (HVOF) thermal spray process for coating deposition with liquid feedstock. The liquid feedstock consists of suspensions and solution precursor injected directly into the combustion chamber of the HVOF gun. The wear performance of the Al2O3 coating produced from metastable Al2O3 feedstock was two order of magnitude better than those of thermally sprayed conventional Al2O3 coatings. The wear rate of the as–sprayed Al2O3 coating was 5.53 x 10–9 mm3 (Nm)–1 and 2.94 x 10–9 mm3(Nm)–1 for the coating heat treated at 600 °C The residual stress of Al2O3 and YSZ coatings studied showed that X-ray diffraction technique is useful to understand the stress state of the top surface of thermal spray coatings; this is particularly useful for contact engineering applications including wear. It was also shown that the through thickness residual stress of a thermal spray coating can be reliably obtained using incremental hole-drilling technique. The average stress state of the Al2O3 coating was compressive in both the longitudinal (-162 MPa) and transverse (-104 MPa) directions as against the tensile stress state in the YSZ coating which has 149 MPa in the longitudinal direction and 102 MPa in the transverse direction. The residual stress in a thermal spray coating was also shown to scale with the building block of the coatings. Another important finding was that thermal spray coating can be made of sintered particles which only undergo thermal softening. The YAG coatings investigated were produced from two feedstock: one from the stoichiometric solution precursor of the nitrates of aluminium and yttrium, the other from YAG suspension. The combination of thermogravimetric analysis, differential scanning calorimetry (TGA/DSC) and X-ray diffraction were used to show the mechanism of formation of YAG from the solution precursor. The YAG topcoat produced from the solution precursor was compared to a YAG coating produced from YAG suspension in terms of microstructure and thermal cycle life performance. The results of the coating formation mechanism provided the YAG formation temperature of the solution precursor under isothermal heating condition or rapidly varied heating during thermal spray process as well as the reaction enthalpies across the formation stages. The formation temperature of YAG obtained was ~940 °C while the overall reaction enthalpy was approximately +916J/g. The microstructure of the YAG coating made from the solution precursor and the one made from YAG suspension showed they were both built from lamella, however, the defects in each of the YAG coatings were different. Compared to the YSZ topcoat, the YAG coatings had better thermal conductivity (SP-YAG had < 1.0 W/m*K while S-YAG had ~1.7 W/m*K) at the elevated temperature investigated but the YSZ coating showed improved thermal cycling life.